Variability management of plugin‐based systems using feature models. (20th July 2016) - Santos, André L.
Summary: Plugin‐based systems are typically realized with resort to a component framework that offers an infrastructure for assembling plugin components, which can be composed to form system variants. Feature models have been proposed as an abstraction to manage software variability, where feature configurations describe variants of a software system. In this paper, we propose an automated approach to map the artifacts of plugin‐based component frameworks to feature models. We describe a methodology for structuring the architecture of a plugin‐based system, so that the variability space and variants are reflected in a feature model and its configurations. We materialized the proposed approach for the Eclipse Equinox component framework in a tool to visualize the variability of plugin‐based systems in feature diagrams, which can be used to generate system variants. We carried out an experiment where we developed a small plugin‐based product line on top of Equinox in the context of an advanced software development course. Copyright © 2016 John Wiley & Sons, Ltd.